El mitin de Toulouse : 11 de marzo de 1945 / [presentación de Enrique de Francisco ; oradores Pascual Tomás, Rodolfo Llopis, Trifón Gómez] - Francisco, Enrique deLlopis, Rodolfo (1895-1983) Gómez San José, Trifón; Tomás, Pascual
Precede al tít.: P.S.O.E., U.G.T., F.J.S.E.